Optimalisation of Home Garden in Babakan Village Cisaat District Sukabumi Regency - Rahayu, Arifah (QARDHUL HASAN: MEDIA PENGABDIAN KEPADA MASYARAKAT, 2015)
Home garden  has many functions, either for food production, children play ground or to conserve water,  land and plant genetic resources.This  programme  aimed to improve the capability  of  women  household  in  home  garden  management. especially to increase household income. The  programme  has succeeded to increase  the use of home garden  well, sustainable  and fairly environment. Basides that the women household have produced many kind of vegetables and fruits. The interesting to apply the extension and training  materials,  and to continue the activities although the programme has finished.